The cross-sectional analytical study of COVID and post COVID mucormycosis in diabetic and non-diabetic patients and their outcomes - Bajad, Vishal; Bansode, M. V.; Paritekar, Anita (International Journal of Research in Medical Sciences, 2024)
Background: Mucormycosis, a rare but serious fungal infection, has shown a concerning rise in incidence among COVID and post-COVID patients, with males constituting majority of cases. This study aimed to investigate the impact of diabetes mellitus (DM) on outcomes in patients with COVID and post-COVID mucormycosis. Given the known association between DM and increased susceptibility to infections, particularly fungal ones, understanding the role of DM in exacerbating mucormycosis outcomes is crucial for clinical management. Methods: A cross-sectional analytical study was conducted, involving a cohort of 50 patients with mucormycosis, equally divided into diabetic and non-diabetic groups. Data on morbidity, complications, hospitalization rates, and mortality were collected and compared between the two groups. Additionally, glycemic control status was assessed among diabetic patients to evaluate its impact on outcomes. Results: Among the 50 patients analyzed, diabetic individuals displayed significantly poorer outcomes compared to their non-diabetic counterparts. This included increased morbidity, complications, hospitalization rates, and mortality. Moreover, patients with uncontrolled DM exhibited the worst outcomes, highlighting the critical importance of managing glycemic control during mucormycosis treatment. Conclusions: The study underscores the necessity of vigilant monitoring and targeted interventions, particularly in diabetic individuals, to mitigate the adverse effects of mucormycosis in the context of COVID-19. Effective management of diabetes, especially glycemic control, is crucial for improving overall patient outcomes and reducing the burden of mucormycosis-related complications and mortality in both COVID and post-COVID scenarios. Further research is warranted to refine treatment protocols and optimize outcomes for this vulnerable population.